Penyusunan Standar Operasional Prosedur Pengoperasian Gardu Induk di PLTP Sarulla Operations Ltd. - Harefa, Jonius Christian (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2023)
Sarulla PLTP (Geothermal Power Plant) is a clean and environmentally friendly renewable energy power plant. Sarulla PLTP has a substation as part of the distribution of electricity from the power plant to the electricity network transmission line PT. PLN Persero. Substation operations must be carried out with safety first. Engineers have a code of ethics in Sapta Dharma which prioritizes safety at work. Safety at work can be achieved if there are good and correct SOP’s (Standard Operating Procedures). In engineering practices that have been carried out, it is known that the Sarulla PLTP does not yet have a standard SOP for operating substations at power plants. During engineering practice, SOP’s for the operation of the 150 kV Sarulla – NIL substation have been prepared with reference to supporting data on PT. PLN Persero substation operating standards. The SOP is prepared in accordance with the existing substation configuration at the Sarulla – NIL PLTP.